Ag-Pd core–shell electrocatalysts for ethanol oxidation and oxygen reduction reactions in alkaline medium. (19th November 2020) - Shi, Jianchao; Wang, Jie; Chen, Yumei; Sun, Yulong; Liu, Baozhong; Fan, Yanping
Abstract: Ag-Pd core–shell nanoparticles with different thickness of Pd shell are successfully prepared applying polyol methods with 1, 2-propanediol as a solvent and reducing agent. A strongly electronic interaction between the sublayer Ag and surface Pd atoms are measured for the Ag-Pd core–shell particles with lower Pd/Ag atom ratios (Pd:Ag ⩽ 3:10), which derives from the near-surface alloying effect. Upon increasing the thickness of Pd shell, the effect of Ag core on surface Pd atoms become weaker, correspondingly the surface Pd atoms present the features closed to pure Pd. All Ag10 @Pdx /C core–shell catalysts exhibit improved ethanol oxidation reaction (EOR) activities compared to pure Pd/C. Here, the EOR activities of Ag10 @Pdx /C catalysts decrease when adding the thickness of the Pd shell, in which the Ag10 @Pdx /C with the lowest Pd/Ag ratios (Pd/Ag = 1:10) shows the highest i p value ten times that of Pd/C. The participation of Ag as a core with low electronegativity and larger lattice constant can increase the electron densities and bring the lattice expansion of surface Pd atoms, due to the electron effect and the geometric effect, which effectively strengthen the bonding energy of reaction species on Pd surface and benefit the OH – adsorption for EOR, especially in lower Pd/Ag ratios than forming a monolayer Pd. For oxygen reduction reaction (ORR), the Ag10 @Pdx /C samples also exhibit enhanced activities than pure Pd/C. Differently, there is a volcanic relation between the mass activities and the Pd/Ag atom ratios, where the Ag10 @Pd3 /C with about a monolayer Pd shell exhibits highest ORR activity. The improved ORR activities may be relay on the appropriate OH – adsorption, the exposed surface Ag atoms and the quick transformation of OH from Pd atoms.